Dendritic cell-targeting chemokines inhibit colorectal cancer progression - Pengkun Yuan; Yunyi Zhou; Zhixue Wang; Liming Gui; Bin Ma (Open Exploration Publishing Inc., 2022)
Aim: Recent progress in cancer immunotherapy has shown its promise and prompted researchers to develop novel therapeutic strategies. Dendritic cells (DCs) are professional antigen-presenting cells crucial for initiating adaptive anti-tumor immunity, therefore a promising target for cancer treatment. Here, anti-tumor activities of DC-targeting chemokines were explored in murine colorectal tumor models. Methods: The correlation of chemokine messenger RNA (mRNA) expression with DC markers was analyzed using The Cancer Genome Atlas (TCGA) dataset. Murine colorectal tumor cell lines (CT26 and MC38) stably overexpressing mouse C-C motif chemokine ligand 3 (CCL3), CCL19, CCL21, and X-C motif chemokine ligand 1 (XCL1) were established by lentiviral transduction. The effect of chemokines on tumor cell proliferation/survival was evaluated in vitro by cell counting kit-8 (CCK-8) assay and colony formation assay. Syngeneic subcutaneous tumor models were used to study the effects of these chemokines on tumor growth. Ki-67 expression in tumors was examined by immunohistochemistry. Immune cells in the tumor microenvironment (TME) and lymph nodes were analyzed by flow cytometry. Results: Expression of the four chemokines was positively correlated with the two DC markers [integrin alpha X (ITGAX) and CLEC9A] in human colorectal tumor samples. Tumoral overexpression of DC-targeting chemokines had little or no effect on tumor cell proliferation/survival in vitro while significantly suppressing tumor growth in vivo. Fluorescence-activated cell sorting (FACS) analysis showed that CCL19, CCL21, and XCL1 boosted the ratios of DCs and T cells in CD45+ leukocytes while CCL3 increased the percentage of CD45+ leukocytes in total cells in MC38 tumor. XCL1 had an additional positive effect on antigen uptake by DCs in the TME and antigen transfer to tumor-draining lymph nodes. Conclusions: CCL3, CCL19, CCL21, and XCL1 exhibited potent anti-tumor activities in vivo, although they might differentially regulate immune cells in the TME and antigen transfer to lymph nodes.